Environmental physiology of Eldana saccharina (Lepidoptera:Pyralidae) in South Africa : implications for pest management - Kleynhans, Elizabeth (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.